WANPRESTASI DALAM PERJANJIAN INVESTASI ANTARA KOPERASI DAN PERORANGAN (STUDI PUTUSAN PENGADILAN NEGERI MEDAN NOMOR 469/PDT.G/2014/PN.MDN) - HERMAN SETIAWAN ZALUKHU (PREMISE LAW JURNAL, 2017)
ABSTRACT Investment Contract between a cooperative and individuals is made after there is an agreement of both parties. The problem is that the cooperative management does not implement the contract (default) toward the individuals who have provided capital as borrowed capital for the cooperative so that the latter will be successful in doing its business in oil. The objective of writing the thesis with the title, “Default in Investment Contract between Cooperative and Individuals (A Case Study on the Medan District Court’s Verdict No. 469/Pdt.G/2014/PN.Mdn),” is to give the description about the form of default in implementing a contract and the form of liability of cooperative management and its legal consequences.The research used juridical normative method which processed only secondary data which consisted of laws, juridical theory, and other sources which were relevant to the theme of the research. Field research and interviews were also conducted to support the data and the theories.The result of the research showed that there were some types of default in the implementation of investment contract between cooperative and individuals who provided borrowed capital for the cooperative. Keywords: Investment Contract, Default, Cooperative and Individual